The Training to Read and Write Calculate is Called with Calistung as an Effort to Eliminate Illness in Community Masiyepi Village, Manokwari District - ardian eko sajaril; Syahira Syahira; Rahmatia Rahmatia; Lisa Handayani; Wida Widaningsih (Peneliti.net, 2020)
Community service activities in the context of eradicating illiteracy in Masiyepi Village, South Manokwari District, Manokwari Regency, aim to describe and improve literacy and numeracy (Calistung) skills of the community in Masiyepi Village. This service activity started on September 2 to November 2, 2019 at Masiyepi Village, South Manokwari District, Manokwari Regency, West Papua. Activities that have been carried out are literacy and arithmetic training using letter cards and shirt buttons. This training had a huge impact so that it was able to improve the literacy and numeracy skills of the people of Masiyepi Village.